2022
DOI: 10.1108/bij-08-2021-0467
|View full text |Cite
|
Sign up to set email alerts
|

Coordination issues in managing the reverse supply chain: a systematic literature review and future research directions

Abstract: PurposeReverse supply chain (RSC) is one of the ways to handle product returns efficiently. Recovery of residual value from product returns also helps in achieving sustainability. Its successful implementation requires coordination among all the channel members involved in the activities, from the acquisition to collection to the disposition of returned products. This article aims to review the literature about coordination issues in the RSC.Design/methodology/approachA systematic literature review of 151 arti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 170 publications
0
6
0
Order By: Relevance
“…Some papers focused on specific waste types in certain RSCs, while others had a more general approach that could be applied to any waste type (called general context). As shown in Figure 4, the majority of the studies identified (17) were related to the general context, while others focused on electric electronic equipment waste -EEEW (3)-and construction and demolition waste-CDW (2). Additionally, eight papers investigated various other waste types.…”
Section: Brief Bibliometric Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Some papers focused on specific waste types in certain RSCs, while others had a more general approach that could be applied to any waste type (called general context). As shown in Figure 4, the majority of the studies identified (17) were related to the general context, while others focused on electric electronic equipment waste -EEEW (3)-and construction and demolition waste-CDW (2). Additionally, eight papers investigated various other waste types.…”
Section: Brief Bibliometric Analysismentioning
confidence: 99%
“…This is evident in recent works. such as [7,12,17,18], and in the specific context of RSCs it is possible to mention [16,19]. In our study, an SLR was conducted, which is distinct from previous reviews as it does not limit the type of waste or its route, whether a closed-loop or open-loop supply chain.…”
Section: Introductionmentioning
confidence: 99%
“…Game theoretical models have been employed in supply chain applications such as inventory management, pricing, and coordination (Agi et al, 2021; Agrawal et al, 2022). When cooperation is lacking, game theory can be used to supplement decision‐making tools.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Various theories (i.e., game theory, stakeholder theory, contract theory, and prospect theory) have been used by researchers in CSC (Lahane et al, 2020). Game theory has received attention from researchers in resolving reverse supply chain coordination issues (Agrawal et al, 2022) and is also a powerful tool for CE (Choi et al, 2020). Game theory can be used to optimize multiplayer, decentralized supply chain organizations.…”
Section: Theoretical Contributionsmentioning
confidence: 99%
“…Literature indicates suppliers as the most critical to effective implementation of GSCM given their role in the sourcing of material and provisions of inputs such as parts and components to manufacturers for the final products (Kafa et al, 2013;Vanalle et al, 2017;Xu, 2019 Feng et al, 2020;Petrudi et al, 2021). While governmental laws and regulations may have huge impact on individual GSCM practices (Zhu et al, 2008;Zailani et al, 2012;Huo et al, 2018), effective collaboration with suppliers will enable the optimal GSCM and sustainability achievement (Zailani et al, 2012;Petrudi et al, 2021;Agrawal et al, 2022).…”
Section: Introductionmentioning
confidence: 99%